'A Chain of Creation, Continuation, Continuity': Feminist dramaturgy and the matter of the sea. (3rd March 2016) - Berger, Cara
Abstract : This article considers what remnants of the imaginary link established between the maternal and the sea may still be useful in feminist performance practice and theory. It does so by discussing a practice-as-research experiment that adapted strategies from Hélène Cixous'sécriture féminine —that performs a liquification of ordering structures in prose writing—into a dramaturgical form based on the logic of waves. The article goes on to suggest that such a dramaturgy recasts creation as a fluid state of becomingex tempore, resisting the masculine-connoted vision of creation as an act of the singular geniusex nihilo . It further argues that drawing on a non-human phenomenon, the sea, to describe and theorize a type of dramaturgical composition may be read as a twofold attempt on the hegemony of patriarchal culture: through its associative link with the maternal body the creative potential of the feminine is revalued while at the same time the generative capacity of the non-human is recognized via Gaston Bachelard's notion of the material imagination. The article concludes by proposing that the sea, together with its analogic association to the maternal, can be instated as a figure that gives temporary shape to an alternative vision of cultural production.